FACTORS RELATED TO HEPATITIS B IN PREGNANT WOMEN - Rani Widiyanti Surya Atmaja (Jurnal Asuhan Ibu dan Anak, 2022)
The prevalence of hepatitis is 0.4% of the population in Indonesia, of which 1-5% are pregnant women with hepatitis B virus. The purpose of this study was to determine the relationship between maternal characteristics, knowledge of hepatitis B, prevention attitudes, family history, immunization history, sexual activity, traditional medicine and rest with the incidence of Hepatitis B in Cirebon Regency in 2020. Analytical study with a case-control approach with Chi-square test and logistic regression. The number of samples using the Stanley Lemeshow formula obtained 42 people, taken by purposive sampling at the Waruroyom and Mundu Health Centers. Family history of hepatitis was only found in pregnant women with hepatitis B, namely 2 people (21.4%) with a p value of 0.32 and an OR value of 3.545 with a confidence interval between 2.149 to 5.850. The majority of pregnant women with hepatitis B did rest 6 hours/day that is 10 people (71.4%) while those who do not have hepatitis B majority do rest <6 hours/day that is 20 people (71.4%) with p value 0.021 and OR value 0.160 with a confidence interval of 0.039 to with 0.662. Variables related to the incidence of Hepatitis B in pregnant women are education, traditional medicine and rest. The greatest and smallest relationship strengths were education (OR:154,324) and rest (OR:18,932). Pregnant women with low education need to be given information or health education about hepatitis.